Based on the Zero Product Property, the correct statement about the quadratic equation \((2x−3)(x+2)=0\) is:
At least one of the factors, (2x−3) or (x+2), must equal 0 for the entire function to equal 0.
This means that in order for the product of those two factors to equal zero, at least one of the factors must itself be equal to zero. Therefore, the corresponding values of \(x\) can be found by solving each factor separately:
- \(2x - 3 = 0\) leads to \(x = \frac{3}{2}\)
- \(x + 2 = 0\) leads to \(x = -2\)
Thus, the equation has two solutions, but only one of the factors needs to be zero for the entire function to equal zero.